2015
DOI: 10.1016/j.imbio.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective estrogen receptor modulators in T cell development and T cell dependent inflammation

Abstract: Lasofoxifene (las) and bazedoxifene (bza) are third generation selective estrogen receptor modulators (SERMs) with minimal estrogenic side effects, approved for treatment of postmenopausal osteoporosis. T cells are involved in the pathology of postmenopausal osteoporosis and previous studies have established an important role for 17β-estradiol (E2) in T cell development and function. E2 causes a drastic thymic atrophy, alters the composition of thymic T cell populations, and inhibits T cell dependent inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
0
17
2
Order By: Relevance
“…This analysis demonstrated neither changes in CD4 + and CD8 + T cells numbers, nor in the proportion of PD-1 high exhausted CD8 + T cells between vehicle or bazedoxifene-treated cohorts (Appendix Fig S4). Similarly, we did not detect differences in either CD45 + , CD11b + ; Ly6C hi, Ly6G lo monocytic, or CD45 + , CD11b + , Ly6C lo , Ly6G hi granulocytic MDSCs, nor in F4/80 + tumorassociated macrophages between the two cohorts (Appendix Fig S5), despite reports that some SERMs may affect neutrophils and decrease lymphopoiesis (Bernardi et al, 2015;Nordqvist et al, 2017). Collectively, these data suggest that the anti-tumor effect of bazedoxifene is primarily mediated by tumor cell-intrinsic mechanism rather than by altering the host's anti-tumor immune response.…”
Section: Bazedoxifene Treatment Does Not Alter Tumor Immune Responsescontrasting
confidence: 59%
“…This analysis demonstrated neither changes in CD4 + and CD8 + T cells numbers, nor in the proportion of PD-1 high exhausted CD8 + T cells between vehicle or bazedoxifene-treated cohorts (Appendix Fig S4). Similarly, we did not detect differences in either CD45 + , CD11b + ; Ly6C hi, Ly6G lo monocytic, or CD45 + , CD11b + , Ly6C lo , Ly6G hi granulocytic MDSCs, nor in F4/80 + tumorassociated macrophages between the two cohorts (Appendix Fig S5), despite reports that some SERMs may affect neutrophils and decrease lymphopoiesis (Bernardi et al, 2015;Nordqvist et al, 2017). Collectively, these data suggest that the anti-tumor effect of bazedoxifene is primarily mediated by tumor cell-intrinsic mechanism rather than by altering the host's anti-tumor immune response.…”
Section: Bazedoxifene Treatment Does Not Alter Tumor Immune Responsescontrasting
confidence: 59%
“…Estrogens and SERMs have vast effects on the immune system, but the mechanisms underlying the antiarthritic effects of E2 and SERMs have not been fully elucidated (11,12,19,20), although we reported that E2 influences localization of proinflammatory T helper 17 cells in arthritis (14). The present study is limited to mostly clinical observa- tions and does not present any mechanisms regarding antiarthritic effects of combined BZA/E2.…”
Section: Discussionmentioning
confidence: 65%
“…The risk of estrogen‐disrupting agents has been a worldwide problem for decades, leading to many studies to identify the toxicologic effects induced by estrogen disruptors in mammals and wildlife species. Recent studies have demonstrated that endocrine disruptors affect not only the reproductive system but also the immune system in mammals (Bernardi et al, 2015; Fukuyama et al, 2010; Fukuyama, Tajima, Hayashi, Ueda, & Kosaka, 2011; Sakazaki, Ueno, & Nakamuro, 2006). As a part of immunotoxicologic events, the interaction between allergy development and exposure to endocrine disruptors has been investigated in several studies (Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%